KAJIAN PELESTARIAN KAMPUNG KAUMAN KUDUS SEBAGAI KAWASAN BERSEJARAH PENYEBARAN AGAMA ISLAM - Nurini, Nurini (Diponegoro University, 2011)
Historic area as a cultural heritage is one of the most precious relic of the past, because of the presence ofbuildings and the character of its surroundings have historical value that displays a visual story of a certainplace. As one of the cities central to the spread of Islam in Java â€œKauman Village, Kudusâ€ has a specialcharacter and a specific Islamic cultural heritage, whether in the form of tangible or intangible heritage and theabstract that needs to be maintained.The purpose of this study is to assess the potential of the cultural heritage of the â€œKauman Village, Kudusâ€ inan effort to preserve and protect cultural heritage based on its characteristic as an area central to the spread ofIslam in the region.